Study on In Situ Stress Distribution Law of the Deep Mine: Taking Linyi Mining Area as an Example - Xuelong Li; Shaojie Chen; Sheng Wang; Meng Zhao; Hui Liu (Advances in Materials Science and Engineering)
The variation of the in situ stress state is closely related to various factors. In situ stress state is also an important indicator to guide mining production. The study of in situ stress measurement and its distribution characteristics has always been a basic and very important work in mine production. In this study, the deep mines of Linyi Mining Area were considered as the research object. In this regard, the stress distribution law of each mine was studied. We found that the relationship between principal stresses was σH > σv > σh, which belongs to the strike-slip stress regime. In this stress regime, the lateral Earth pressure coefficient was greater than one, and the magnitude of the three principal stresses all showed an increasing trend with the increase of depth. The maximum horizontal stress direction of the Gucheng Coal Mine, Guotun Coal Mine, and Pengzhuang Coal Mine was NW-SE under the influence of regional geological structure, while the maximum horizontal stress direction of Wanglou Coal Mine was NE-SW under the influence of local geological structure. Besides, the relationship between mine in situ stress and mine geological structure, the impact of original rock stress on stope stability, and the effect of original rock stress on floor water inrushing were also investigated. We believe that the research results are beneficial to mine disaster prevention and safety production.